Science of International Law and Regional Orders: A Critical Appraisal of Alejandro Álvarez and Carl Schmitt - Simonyan, Artur (Revista Tribuna Internacional, 2023)
In this article, I deconstruct the legal science of Alejandro Alvarez – a Chilean jurist – and Carl Schmitt – a German constitutional and international law scholar – to represent the normative traces of the theoretical construct of regional international law. The article revisits Schmittian grossräume concept and Alvarez’s American international law as empirical evidence of normative deliberations of regionalism’s functionality in international law. It then concludes that both theories that hinge on the Monroe Doctrine have envisioned distinct patterns of regional international law: vertical-apologetic and horizontal-utopian. It finally elucidates the scientific relevance of revisiting their scholarship and provides an alternative viewing to the brute generalizations that depict regionalism as a challenge to the unity of international law.